Pancreas volume and fat fraction in children with Type 1 diabetes. Issue 10 (15th April 2016) - Regnell, S. E.; Peterson, P.; Trinh, L.; Broberg, P.; Leander, P.; Lernmark, Å.; Månsson, S.; Elding Larsson, H.
Abstract: Aims: People with Type 1 diabetes have smaller pancreases than healthy individuals. Several diseases causing pancreatic atrophy are associated with pancreatic steatosis, but pancreatic fat in Type 1 diabetes has not been measured. This cross‐sectional study aimed to compare pancreas size and fat fraction in children with Type 1 diabetes and controls. Methods: The volume and fat fraction of the pancreases of 22 children with Type 1 diabetes and 29 controls were determined using magnetic resonance imaging. Results: Pancreas volume was 27% smaller in children with diabetes (median 34.9 cm 3 ) than in controls (47.8 cm 3 ; P < 0.001). Pancreas volume correlated positively with age in controls ( P = 0.033), but not in children with diabetes ( P = 0.649). Pancreas volume did not correlate with diabetes duration, but it did correlate positively with units of insulin/kg body weight/day ( P = 0.048). A linear model of pancreas volume as influenced by age, body surface area and insulin units/kg body weight/day found that insulin dosage correlated with pancreas volume after controlling for both age and body surface area ( P = 0.009). Pancreatic fat fraction was not significantly different between the two groups (1.34% vs. 1.57%; P = 0.891). Conclusions: Our findings do not indicate that pancreatic atrophy in Type 1 diabetes is associated with an increased pancreatic fat fraction, unlike some other diseases featuring reduced pancreatic volume. We speculate that our results may support the hypotheses that much of pancreatic atrophy in Type 1 diabetes occurs before the clinical onset of the disease and that exogenous insulin administration decelerates pancreatic atrophy after diabetes onset. What's new?: Children with Type 1 diabetes have smaller pancreases than controls, yet pancreas size is unrelated to diabetes duration. Exogenous insulin administration may decelerate the decline in pancreas size in Type 1 diabetes. We found no difference in fat fraction between children with Type 1 diabetes and controls.